2001
DOI: 10.1111/j.1151-2916.2001.tb00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Substituted Pollucites Along the CsAlSi2O6–CsTiSi2O6.5 Join: A High‐Temperature Calorimetric Study

Abstract: Enthalpies of drop solution for a suite of substituted pollucites with the compositions CsTi x Al 1؊x Si 2 O 6؉0.5x , 0 < x < 1, which are synthesized using the sol-gel method, have been measured in molten lead borate (2PbO⅐B 2 O 3 ) at 701°C. As Ti 4؉ substitutes for Al 3؉ , the enthalpies of drop solution become less endothermic and show exothermic heats of mixing within the composition range from x ‫؍‬ 0.3 to 1. This nonideal mixing behavior is consistent with the trend seen in variation of lattice paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…10 Most studies related to the Cs/Sr-loaded titanosilicate waste forms have focused on their structure and selectivity. [11][12][13][14][15] What is still lacking in this area is a fundamental understanding of the thermodynamics of the titanosilicate waste forms. Moreover, the relations among crystalline and amorphous or glassy states for waste forms are important due to the possibility of producing material instability through amorphization from radiation damage and during vitrification.…”
Section: Introductionmentioning
confidence: 99%
“…10 Most studies related to the Cs/Sr-loaded titanosilicate waste forms have focused on their structure and selectivity. [11][12][13][14][15] What is still lacking in this area is a fundamental understanding of the thermodynamics of the titanosilicate waste forms. Moreover, the relations among crystalline and amorphous or glassy states for waste forms are important due to the possibility of producing material instability through amorphization from radiation damage and during vitrification.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative strategy is to immobilize the radionuclides as components in the crystal structures of dense minerals, such as silicate, phosphate, and titanate [9][10][11][12][13][14][15][16]. Compared to glass waste forms, these dense minerals have robust thermal stability and aqueous durability rendering them viable candidates for hosting radionuclides.…”
Section: Introductionmentioning
confidence: 99%
“…Cs 0.21 Al 2.44 Ti 5.53 -O 16 , Ba 1.17 Rb 0.19 Al 2.46 Ti 5.53 O 16 , and Ba 1.14 Sr 0.10 Al 2.38 Ti 5.59 O16 using electron microprobe analysis (EMPA). Synchrotron X-ray diffraction (XRD) combined with Rietveld analysis showed that all the three hollandites adopt a tetragonal symmetry with the space group I4/m[11].…”
mentioning
confidence: 99%
“…1,2 Substituting Ti 4ϩ for Al 3ϩ over the tetrahedral sites, accompanied by the incorporation of extra O 2into the structure to achieve its charge neutrality, produces a series of substituted pollucites with the general formula CsTi x Al 1-x Si 2 O 6ϩ0.5x , 0 Յ x Յ 1. 3,4 This group of materials is of considerable interest for practical applications and from the viewpoint of crystal chemistry.…”
Section: Introductionmentioning
confidence: 99%